Case Report: Immune-mediated acute liver failure induced by tislelizumab in a patient with advanced cervical cancer - Liu, Chaoxia; Li, Xinchun; Deng, Yuping (Frontiers in Oncology, 2025)
Tislelizumab, an anti-PD-1 monoclonal antibody, is associated with immune-related hepatitis in 1.8% of cases, but reports of acute liver failure (ALF) remain exceedingly rare. We present a case of fulminant hepatitis and ALF following Tislelizumab therapy in a 55-year-old woman with locally advanced cervical adenocarcinoma. After three cycles of concurrent chemoradiotherapy and Tislelizumab, she developed grade 4 immune-mediated hepatitis and ALF following a fourth Tislelizumab dose, marked by severe transaminitis (AST 5329 U/L, ALT 2384 U/L), coagulopathy (INR 5.85), hyperbilirubinemia (TBIL 56.99 IU/L), and hepatic encephalopathy. Management included plasma exchange, continuous hemofiltration, high-dose corticosteroids, and immunosuppressive agents. Despite aggressive intervention, the patient’s condition deteriorated, underscoring the rapid progression of Tislelizumab-induced hepatotoxicity. This case highlights the critical need for vigilant monitoring of high-risk patients receiving immune checkpoint inhibitors and early intervention for suspected immune-mediated liver injury.